POLISH-RUSSIAN WAR UNDER THE STAR-SPANGLED BANNER – TRANSLATION OF MASŁOWSKA’S LANGUAGE INTO ENGLISH - Chyrzyński, Tomasz (Acta Neophilologica, 2010)
The article is devoted to the analysis of English translation of non-standard language in Wojna polsko-ruska pod flagą biało-czerwoną by Masłowska. The decisions made by the translator were investigated in terms of Hejwowski’s techniques of translating language varieties. The analysis of chosen expressions proves that in most cases the translator decided to adapt the text to the target readership and rather resigned from the author-oriented rendering. It shows that a culture-specific novel is intelligible for the target reader when the language is lucid.